ORGAN DONATION AND TRANSPLANTATION IN THE RUSSIAN FEDERATION IN 2013 6th report of National Register - S.V. Gautier; Y.G. Moysyuk; S.M. Khomyakov (Вестник трансплантологии и искусственных органов)
Aim. To carry out monitoring of the state and prospects of the development of organ donation and transplantation in the Russian Federation according to 2013. Materials and methods. Questioning of heads of all the centers of transplantation is carried out. The comparative analysis of the obtained data in dynamics of years, between certain regions of the Russian Federation, the transplantation centers, and also with data of the international registers is made. Results. According to the register in 2013 in the Russian Federation functioned 35 centers of kidney transplantation, 15 centers of liver transplantation and 10 centers of heart transplantation. The waiting list of kidney transplantation included more than 4000 potential recipients that makes 15–16% of total number of the patients receiving dialysis. The rate of donor activity made 2,9 per million population (pmp). Effi ciency of donor programs continues to increase: the share of effective donors after brain death in 2013 increased to 72,4%, the share of multiorgan explantation increased to 52,9%, average number of organs received from one effective donor made 2,6. The rate of kidney transplantation made 6,5 pmp, the rate of liver transplantation made 1,9 pmp; the rate of heart transplantation made 1,1 pmp. In the Russian Federation the number of transplantations of liver and heart continues to increase. The signifi cant contribution to development of the organ donation and transplantation brings the Moscow region in which 11 centers of transplantation function and nearly a half of all kidney transplantations and 70% of all liver and heart transplantations are carried out. In 2013 Ministry of Health of Russia continued development of the new federal law «On donation of human organs and their transplantation». Under the auspices of the Russian Transplant Society 11 clinical guidelines about organ donation and transplantation were developed and approved. Together with earlier approved orders and standards of medical care clinical guidelines make methodical base for clinical work in transplantology. Conclusion. The main source of further increase in the number of organ transplantation in the Russian Federation (according to real requirement) is, in our opinion, opening of new programs in regions and development of interregional coordination.